Quality of life in patients with obstructive sleep apnea: Results from the study of health in Pomerania. (21st August 2022) - Vogler, Katharina; Daboul, Amro; Obst, Anne; Fietze, Ingo; Ewert, Ralf; Biffar, Reiner; Krüger, Markus
Summary: Obstructive sleep apnea is known to be an overall public health problem that, among other things, increases morbidity and mortality. Risk factors as well as symptoms of this multidimensional sleep‐related breathing disorder negatively affect quality of life. With our study we aimed to expose the association between obstructive sleep apnea and quality of life in the population of Pomerania, Germany. We utilized data from the population‐based Study of Health in Pomerania (SHIP). Information on health status and risk factors about 4420 participants (2275 women) were gathered within the cohort SHIP‐TREND, of which 1209 (559 women) underwent an overnight polysomnography and completed sleep questionnaires. The quality of life of the participants was measured using the Short‐Form 12 questionnaire. For our study, an ordinal regression analysis with age, sex, body mass index and the Short‐Form 12 health survey as predictors for apnea–hypopnea index was computed. The potential factors affecting quality of life are different between physical and mental dimensions of quality of life. Significant effects were found regarding age, sex, body mass index and the Short‐Form 12 Mental Component Score, but not the Physical Component Score.